Graphene composite modified asphalt concrete material for ultrathin overlay and preparation method of graphene composite modified asphalt concrete material
Through the composite and preparation method of graphene composite modified asphalt concrete materials, the existing materials are solved to meet the requirements of heavy-duty traffic resistance, dynamic stability and high temperature stability, and the excellent performance of concrete materials is achieved.
Patent Information
- Application Number
- CN202411627746.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The existing asphalt concrete materials for ultra-thin covers are difficult to meet the requirements of heavy-duty traffic against degeneration, dynamic stability and high temperature stability.
Graphene composite modified asphalt concrete material is used to combine petroleum asphalt, activated rubber powder, SBS modifier, stabilizer, additive, PVDF, modified basalt fiber, graphene oxide powder and ceramic powder, and Concrete materials with excellent properties are prepared by premixing and stirring, over-grinding shearing and development steps.
It realizes the super-strong oil film bonding force, excellent high temperature stability, resistance to degeneration and dynamic stability of concrete materials, and can meet the performance needs of heavy-duty traffic.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of asphalt concrete preparation, and in particular to a graphene composite modified asphalt concrete material for ultra-thin overlay and a preparation method thereof. Background Art
[0002] Thin-layer overlay is a relatively new technology in the preventive maintenance technology of pavement surface. This technology can be applied to both asphalt pavement and cement pavement, reflecting the universality of thin-layer overlay technology. The thickness of ordinary thin-layer overlay is only 20mm to 25mm, and it has many advantages such as noise reduction, anti-skid, rapid drainage, convenient construction, low cost, and fast traffic opening. While improving driving comfort and safety, thin-layer overlay can achieve energy conservation and emission reduction, low carbon and environmental protection during construction, and has gradually developed into a very promising form of high-grade highway maintenance.
[0003] At present, asphalt concrete for ultra-thin overlays is mostly mixed with SBS modified asphalt, which can meet the performance requirements of medium and light transportation. However, relying solely on SBS modified asphalt materials is difficult to meet the current heavy-duty transportation requirements for anti-deformation and dynamic stability. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and to provide a graphene composite modified asphalt concrete material for ultra-thin overlay and a preparation method thereof. The concrete material has super strong oil film adhesion, excellent high temperature stability, high and low temperature resistance to deformation and dynamic stability, and can meet the requirements of heavy-load traffic.
[0005] The technical purpose of the present invention is achieved through the following technical solutions: A graphene composite modified asphalt concrete material for ultra-thin overlay, comprising the following components in parts by weight: 70-85 parts of petroleum asphalt, 18-25 parts of activated rubber powder, 1.5-2.5 parts of SBS modifier, 0.15-0.25 parts of stabilizer, 0.1-0.3 parts of additives, 0.5-1 parts of PVDF, 0.5-1 parts of modified basalt fiber, 0.6-1 parts of graphene oxide powder and 0.3-1 parts of ceramic powder.
[0006] As some possible implementation methods of the present application, the concrete material includes the following components in parts by weight: 73-83 parts of petroleum asphalt, 20-23 parts of activated rubber powder, 1.8-2.3 parts of SBS modifier, 0.18-0.2 parts of stabilizer, 0.15-0.25 parts of additives, 0.6-0.9 parts of PVDF, 0.6-0.8 parts of modified basalt fiber, 0.7-0.9 parts of graphene oxide powder and 0.4-0.8 parts of ceramic powder.
[0007] As some possible implementation methods of the present application, the concrete material includes the following components in parts by weight: 80 parts of petroleum asphalt, 20 parts of activated rubber powder, 2 parts of SBS modifier, 0.18 parts of stabilizer, 0.2 parts of additive, 0.9 parts of PVDF, 0.8 parts of modified basalt fiber, 0.8 parts of graphene oxide powder and 0.7 parts of ceramic powder.
[0008] As some possible implementation methods of the present application, the ceramic powder is selected from zirconium oxide, aluminum oxide, magnesium oxide, silicon carbide, silicon nitride, and boron nitride; and the particle size of the ceramic powder is 50-500 nm.
[0009] As some possible implementation methods of the present application, the ceramic powder is subjected to low-temperature plasma modification treatment.
[0010] As some possible implementation methods of the present application, the stabilizer is sulfur; the auxiliary agent is rubber oil; and the petroleum asphalt is No. 70.
[0011] In addition, to achieve the above-mentioned purpose, the present application also provides a method for preparing a graphene composite modified asphalt concrete material for an ultra-thin overlay, comprising the following steps: S1 Premixing and stirring: Premixing and stirring: First, mix PVDF, modified basalt fiber, graphene oxide, ceramic powder and additives, and after they are evenly dispersed, add petroleum asphalt and SBS modifier and stir thoroughly; S2 Grinding and shearing: The material fully stirred in step S1 is subjected to high temperature and high pressure colloid grinding. After sufficient grinding, activated rubber powder is added and ground again; S3 Development: Add a stabilizer to the material that has been ground in step S2 for development, and obtain a graphene composite modified asphalt concrete material after the development.
[0012] As some possible implementation methods of the present application, the grinding shearing time is 15-30 minutes, the grinding temperature is 180-200° C., and the grinding pressure is above 5 atmospheres.
[0013] As some possible embodiments of the present application, the development temperature is 180-190°C.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The present application prepares a concrete material having super strong oil film adhesion, excellent high temperature stability, anti-deformation and dynamic stability by compounding petroleum asphalt, activated rubber powder, SBS modifier, stabilizer, additive, PVDF, modified basalt fiber, graphene oxide powder and ceramic powder. Specifically, the oil film thickness of the concrete material is ≥12.8μm, the dynamic stability is not less than 7235 times / mm, the low temperature fission resistance is not less than 3301με, and it has significant high temperature stability and low temperature fission resistance, and can meet the requirements of heavy load transportation. DETAILED DESCRIPTION
[0015] At present, asphalt concrete for ultra-thin overlays is mostly mixed and produced with SBS modified asphalt, which can meet the maintenance requirements of medium and light traffic. However, relying solely on SBS modified asphalt materials is difficult to meet the current heavy-duty traffic requirements for high temperature stability, anti-deformation, and dynamic stability.
[0016] Based on this, the present application provides a graphene composite modified asphalt concrete material for an ultra-thin overlay, comprising the following components in parts by weight: 70-85 parts of petroleum asphalt, 18-25 parts of activated rubber powder, 1.5-2.5 parts of SBS modifier, 0.15-0.25 parts of stabilizer, 0.1-0.3 parts of additives, 0.5-1 parts of PVDF, 0.5-1 parts of modified basalt fiber, 0.6-1 parts of graphene oxide powder and 0.3-1 parts of ceramic powder; Among the above components, SBS modifier is widely used in asphalt modification due to its good low temperature resistance, air permeability and anti-slip properties. The dynamic stability of the basic concrete system modified by SBS is mostly less than 2500 times / mm, and the low temperature crack resistance is less than 1800με, which is difficult to meet the current heavy-duty traffic requirements for high temperature stability, anti-deformation, and dynamic stability; in addition, the added SBS modifier and asphalt are quite different in chemical structure and relative molecular mass, so the actual compatibility between the two is poor, and the two-phase separation phenomenon is easy to occur at high temperature.
[0017] Based on this, the present application adds modified basalt fiber and PVDF to the above-mentioned basic concrete system. The modified basalt fiber, as a reinforcing material, can shuttle and fill into the matrix, play a role as a skeleton, and can effectively improve the mechanical strength and toughness of the concrete system, as well as prevent the generation of microcracks; PVDF has extremely strong resistance to high and low temperatures, wear resistance, high mechanical strength and toughness. After the addition of the two, the dynamic stability and crack resistance can be significantly increased, thereby effectively improving the high temperature stability, resistance to deformation, and dynamic stability of the concrete system. Although the addition of modified basalt fiber and PVDF can improve the compatibility of the system to a certain extent, the improvement in strength is limited, and it is difficult to meet actual needs. Moreover, cracks still occur after a period of use in heavy-duty traffic, which seriously affects the road surface conditions and makes it difficult to meet the performance requirements of heavy-duty traffic.
[0018] Based on this, the present application adds graphene oxide on the basis of the above components. Graphene oxide has the characteristics of anisotropy and can form a stable cross-network structure in the asphalt system. At the same time, it is embedded in the concrete system to play a skeleton role, thereby improving the dynamic stability and low-temperature crack resistance of the concrete system. At the same time, it contains a large number of active oxygen-containing functional groups such as hydroxyl, epoxy, and carboxyl groups, which can form hydrogen bonds with modified basalt fibers and PVDF, thereby further improving the binding force and compatibility of the components in the concrete system.
[0019] However, after adding the above components, the overall viscosity of the concrete system increases, which leads to a relatively high discharge temperature. The ultra-thin cover is thin due to its thin thickness and the strong thermal conductivity of graphene oxide between components, which leads to a relatively fast overall cooling. The construction, paving and rolling connection requirements are high, and it is easy to have technical problems such as low strength of the cover structure, serious water seepage, and poor performance due to insufficient compaction. Modified basalt fiber has good thermal insulation materials and can reduce the cooling rate, but its addition amount is small and the thermal insulation effect is limited. Therefore, it is necessary to add some other thermal insulation materials to further improve the overall thermal insulation effect of the asphalt system. Based on this, the present application continues to add nano-ceramic powder on the basis of the above components. Its synergistic modified basalt fiber can significantly improve the thermal insulation performance of petroleum asphalt, thereby effectively avoiding the excessive cooling rate of the concrete system, resulting in technical problems such as low strength of the cover structure and water seepage due to insufficient compaction during actual laying. In addition, the added nano-ceramic powder can also further improve the high temperature stability and low temperature anti-fission performance of concrete.
[0020] Through the synergistic effect of the above components, the prepared concrete material can have excellent high-temperature stability, anti-deformation, and dynamic stability, meeting the performance requirements of heavy-load transportation.
[0021] In order to further improve the high temperature stability, anti-deformation and dynamic stability of the concrete material, as some possible implementation methods of the present application, the amount of each component in the concrete material is further limited, that is, the concrete material includes the following components in parts by weight: 73-83 parts of petroleum asphalt, 20-23 parts of activated rubber powder, 1.8-2.3 parts of SBS modifier, 0.18-0.2 parts of stabilizer, 0.15-0.25 parts of additives, 0.6-0.9 parts of PVDF, 0.6-0.8 parts of modified basalt fiber, 0.7-0.9 parts of graphene oxide powder and 0.4-0.8 parts of ceramic powder.
[0022] In order to further improve the high temperature stability, anti-deformation and dynamic stability of the concrete material, as some possible implementation methods of the present application, the amount of each component in the concrete material is further limited, that is, the concrete material includes the following components in parts by weight: 80 parts of petroleum asphalt, 20 parts of activated rubber powder, 2 parts of SBS modifier, 0.18 parts of stabilizer, 0.2 parts of additive, 0.9 parts of PVDF, 0.8 parts of modified basalt fiber, 0.8 parts of graphene oxide powder and 0.7 parts of ceramic powder.
[0023] In order to further improve the high temperature stability, resistance to deformation, and dynamic stability of the concrete material, as some feasible implementation methods of the present application, the amount of each component in the concrete material is further limited, that is, the ceramic powder is selected from zirconium oxide, aluminum oxide, magnesium oxide, silicon carbide, silicon nitride, and boron nitride; the particle size of the ceramic powder is 50-500nm.
[0024] In order to effectively improve the dispersion effect of ceramic powders, as some feasible implementation methods of the present application, the ceramic powders are further processed, that is, the ceramic powders are modified by low-temperature plasma. In this scheme, the surface of the ceramic powder is modified by low-temperature plasma irradiation technology, which can make the ceramic powder present a good dispersion effect in the concrete material and improve the bonding effect with other components. Specifically, the plasma treatment method is: the ceramic powder is placed in a vacuum reaction tank of a low-temperature plasma treatment equipment, the air pressure is pumped to 5 Pa, and then oxygen is introduced, and the vacuum valve is adjusted to keep the vacuum degree at 80 Pa; then the RF power supply is turned on, and the RF power is adjusted to 320 watts to ionize the gas in the reaction tank and produce a glow discharge.
[0025] In order to further improve the high temperature stability, anti-deformation and dynamic stability of concrete materials, as some feasible implementation methods of the present application, the types of stabilizers, additives and petroleum asphalt in the concrete material are further limited, that is, the stabilizer is sulfur; the additive is rubber oil; and the petroleum asphalt is No. 70.
[0026] In addition, to achieve the above-mentioned purpose, the present application also provides a method for preparing a graphene composite modified asphalt concrete material for an ultra-thin overlay, comprising the following steps: S1 Premixing and stirring: Premixing and stirring: first mix PVDF, modified basalt fiber, graphene oxide, ceramic powder and additives, disperse them evenly, then add petroleum asphalt and SBS modifier and stir them thoroughly; S2 Grinding and shearing: The material fully stirred in step S1 is subjected to high temperature and high pressure colloid grinding. After sufficient grinding, activated rubber powder is added and ground again; S3 Development: Add a stabilizer to the material that has been ground in step S2 for development, and obtain a graphene composite modified asphalt concrete material after the development.
[0027] The preparation process of concrete materials includes three parts: premixing, shearing and development. In the premixing stage, PVDF, modified basalt fiber, graphene oxide, ceramic powder and additives are first premixed and stirred to achieve the purpose of dispersing PVDF, modified basalt fiber, graphene oxide and ceramic powder in the additives; then petroleum asphalt and SBS modifier are added and stirred to achieve the dispersion of PVDF, modified basalt fiber, graphene oxide and ceramic powder in the asphalt; finally, concrete material is obtained after grinding and development. The whole preparation process is simple and suitable for industrial production.
[0028] As some possible implementation methods of the present application, the grinding shearing time is 15-30 minutes, the grinding temperature is 180-200° C., and the grinding pressure is above 5 atmospheres.
[0029] As some possible implementation methods of the present application, the development temperature is 180-190°C. During the preparation of asphalt concrete, agglomeration was found. The reason was analyzed as follows: the viscosity of graphene composite modified asphalt was relatively large, the asphalt heating temperature was relatively low, and there was a lot of local adhesion of mineral powder, resulting in agglomeration. By controlling the asphalt heating temperature at 180-190°C, the agglomeration phenomenon disappeared, and the mixture was mixed evenly and transparently.
[0030] The specific preparation of the concrete material described in this application is further described in detail below in conjunction with specific implementation methods.
[0031] Example 1 S1 Premixing: First, fully mix 0.5 parts of PVDF, 0.5 parts of modified basalt fiber (basalt fiber modified by alkane coupling agent KH550), 0.8 parts of graphene oxide powder and 0.7 parts of alumina powder with 0.3 parts of rubber oil. After uniform dispersion, add 80 parts of No. 70 petroleum asphalt and 2 parts of SBS modifier and fully mix; S2 Grinding and shearing: The material fully stirred in step S1 is subjected to high temperature and high pressure colloid grinding. The grinding and shearing time is 15 minutes, the grinding temperature is 180-200°C, and the grinding pressure is above 5 atmospheres. After sufficient grinding, 21 parts of activated rubber powder are added and ground again for 15 minutes. S3 Development: 0.2 parts of sulfur are added to the material that has been ground in step S2 for development. The development temperature is 180-190° C. and the development time is 6 hours. After the development is completed, a graphene composite modified asphalt concrete material is obtained.
[0032] The main properties of the prepared concrete material are: oil film thickness ≥ 12.8 μm, dynamic stability of 7235 times / mm, and low-temperature crack resistance of 3301 με.
[0033] Example 2 S1 Premixing: First, 0.8 parts of PVDF, 0.6 parts of modified basalt fiber (basalt fiber modified by alkane coupling agent KH550), 0.7 parts of graphene oxide powder and 0.8 parts of alumina powder are fully mixed with 0.25 parts of rubber oil. After uniform dispersion, 81 parts of No. 70 petroleum asphalt and 2.1 parts of SBS modifier are added and fully mixed. S2 Grinding and shearing: The material fully stirred in step S1 is subjected to high temperature and high pressure colloid grinding. The grinding and shearing time is 15 minutes. The grinding temperature is 180-200°C and the grinding pressure is above 5 atmospheres. After sufficient grinding, 20 parts of activated rubber powder are added and ground again for 15 minutes. S3 Development: 0.18 sulfur is added to the material after grinding in step S2 for development. The development temperature is 180-190° C. and the development time is 6 hours. After the development is completed, a graphene composite modified asphalt concrete material is obtained.
[0034] The main properties of the prepared concrete material are: oil film thickness ≥ 12.8 μm, dynamic stability of 7257 times / mm, and low-temperature crack resistance of 3312 με.
[0035] Example 3 S1 Premixing: First, fully mix 0.9 parts of PVDF, 0.8 parts of modified basalt fiber (basalt fiber modified by alkane coupling agent KH550), 0.8 parts of graphene oxide powder, 0.7 parts of alumina powder and 0.2 parts of rubber oil. After uniform dispersion, add 80 parts of No. 70 petroleum asphalt and 2 parts of SBS modifier and fully mix; S2 Grinding and shearing: The material fully stirred in step S1 is subjected to high temperature and high pressure colloid grinding. The grinding and shearing time is 15 minutes. The grinding temperature is 180-200°C and the grinding pressure is above 5 atmospheres. After sufficient grinding, 20 parts of activated rubber powder are added and ground again for 15 minutes. S3 Development: 0.18 parts of sulfur are added to the material that has been ground in step S2 for development. The development temperature is 180-190° C. and the development time is 6 hours. After the development is completed, a graphene composite modified asphalt concrete material is obtained.
[0036] The main properties of the prepared concrete material are: oil film thickness ≥ 12.8 μm, dynamic stability of 7280 times / mm, and low-temperature crack resistance of 3320 με.
[0037] Comparative Example 1 (without graphene oxide) Compared with Example 3, the graphene oxide is replaced by modified basalt fiber, and the other components, amounts, and preparation methods remain unchanged.
[0038] The main properties of the prepared concrete material are: oil film ≤9μm, dynamic stability 4981 times / mm, and low-temperature fission resistance 2385με.
[0039] Comparative Example 2 (without modified basalt fiber and PVD) Compared with Example 3, the modified basalt fiber and PVDF are replaced by graphene oxide, and the other components, amounts, and preparation methods remain unchanged.
[0040] The main properties of the prepared concrete material are: oil film ≤9μm, dynamic stability 5133 times / mm, low-temperature fission resistance 2407με.
[0041] From the performance of the concrete materials in Examples 1-3 and Comparative Examples 1-2, it can be seen that the concrete materials in Examples 1-3 are prepared strictly in accordance with the components, dosages and processes provided in this application, and the oil film thickness is ≥12.8μm, the dynamic stability is not less than 7235 times / mm, and the low-temperature fission resistance is not less than 3301με, and has significant high-temperature stability and low-temperature fission resistance.
[0042] In Comparative Example 1, in which no graphene oxide is added, the oil film thickness, dynamic stability and low-temperature fission resistance are all worse than those of Examples 1-3. Even if the amount of modified basalt fiber is increased, the performance is still relatively low. It can be seen that it is difficult to effectively improve the performance of concrete materials simply by relying on the amount of added components.
[0043] In Comparative Example 2, modified basalt fiber and PVDF were not added, and its oil film thickness, dynamic stability and low-temperature fission resistance were worse than those of Examples 1-3. Even if the amount of graphene oxide was increased, the performance was still low. It can be seen that it is difficult to effectively improve the performance of concrete materials simply by relying on the amount of added components.
Claims
1. A graphene composite modified asphalt concrete material for ultra-thin overlay, characterized in that: It includes the following components by weight: 70-85 parts of petroleum asphalt, 18-25 parts of activated rubber powder, 1.5-2.5 parts of SBS modifier, 0.15-0.25 parts of stabilizer, 0.1-0.3 parts of additives, 0.5-1 parts of PVDF, 0.5-1 parts of modified basalt fiber, 0.6-1 parts of graphene oxide powder and 0.3-1 parts of ceramic powder.
2. The graphene composite modified asphalt concrete material for ultra-thin overlay according to claim 1, characterized in that: It includes the following components by weight: 73-83 parts of petroleum asphalt, 20-23 parts of activated rubber powder, 1.8-2.3 parts of SBS modifier, 0.18-0.2 parts of stabilizer, 0.15-0.25 parts of additives, 0.6-0.9 parts of PVDF, 0.6-0.8 parts of modified basalt fiber, 0.7-0.9 parts of graphene oxide powder and 0.4-0.8 parts of ceramic powder.
3. The graphene composite modified asphalt concrete material for ultra-thin overlay according to claim 1, characterized in that: It includes the following components by weight: 80 parts of petroleum asphalt, 20 parts of activated rubber powder, 2 parts of SBS modifier, 0.18 parts of stabilizer, 0.2 parts of additive, 0.9 parts of PVDF, 0.8 parts of modified basalt fiber, 0.8 parts of graphene oxide powder and 0.7 parts of ceramic powder.
4. The graphene composite modified asphalt concrete material for ultra-thin overlay according to claim 1, characterized in that: The ceramic powder is selected from zirconium oxide, aluminum oxide, magnesium oxide, silicon carbide, silicon nitride, and boron nitride; and the particle size of the ceramic powder is 50-500 nm.
5. The graphene composite modified asphalt concrete material for ultra-thin overlay according to claim 1, characterized in that: The ceramic powder is modified by low-temperature plasma.
6. The graphene composite modified asphalt concrete material for ultra-thin overlay according to claim 1, characterized in that: The stabilizer is sulfur; the auxiliary agent is rubber oil; and the petroleum asphalt is No.
70.
7. The method for preparing a graphene composite modified asphalt concrete material for ultra-thin overlay according to any one of claims 1 to 6, characterized in that: The steps include: S1 Premixing: First, mix PVDF, modified basalt fiber, graphene oxide, ceramic powder and additives, disperse them evenly, then add petroleum asphalt and SBS modifier and stir them thoroughly; S2 Grinding and shearing: The material fully stirred in step S1 is subjected to high temperature and high pressure colloid grinding. After sufficient grinding, activated rubber powder is added and ground again; S3 Development: Add a stabilizer to the material that has been ground in step S2 for development, and obtain a graphene composite modified asphalt concrete material after the development.
8. The method for preparing a graphene composite modified asphalt concrete material for ultra-thin overlay according to claim 7, characterized in that: The grinding shearing time is 15-30 minutes, the grinding temperature is 180-200°C, and the grinding pressure is above 5 atmospheres.
9. The method for preparing a graphene composite modified asphalt concrete material for ultra-thin overlay according to claim 7, characterized in that: The growth temperature is 180-190℃.
Citation Information
Patent Citations
Modified rubber asphalt and preparing method thereof
CN109627794A
Compact ultrathin overlay asphalt mixture and preparation method thereof
CN113912329A
Graphene oxide and rubber composite modified asphalt used under large-temperature-difference climate condition and preparation method of graphene oxide and rubber composite modified asphalt
CN114213853A
Ultrathin overlay composite modified asphalt concrete and preparation method thereof
CN116119979A
Modified asphalt composition and modified asphalt mixture, and method for producing them
JP2016210878A
Cited By
Environment-friendly high-strength asphalt concrete and preparation method thereof
CN120058280A
Ultrathin asphalt material with high skid resistance and preparation method thereof
CN120842869A